2015
DOI: 10.5194/cp-11-571-2015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Sahara desertification on Arctic cooling during the Holocene

Abstract: Abstract. Since the start of the Holocene, temperatures in the Arctic have steadily declined. This has been accredited to the orbitally forced decrease in summer insolation reconstructed over the same period. However, here we present climate modelling results from an Earth model of intermediate complexity (EMIC) that indicate that 17-40 % of the cooling in the Arctic, over the period 9-0 ka, was a direct result of the desertification that occurred in the Sahara after the termination of the African Humid Period… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
2
4
0
1
Order By: Relevance
“…Alternatively, potential biases in the models may result from imprecise estimation of the climate sensitivity to forcing factors and the incomplete representation of feedback processes 5 , 39 . Previous studies have suggested that feedbacks in response to insolation forcing, such as vegetation 18 , 40 43 , sea ice 44 47 , clouds 18 , and dust 48 , 49 , may have large impacts on temperatures, especially winter temperatures 18 , 41 43 , 46 . Although most of these feedbacks were incorporated into the TraCE-21ka simulation 5 , there are large uncertainties on feedbacks in the models 18 , 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, potential biases in the models may result from imprecise estimation of the climate sensitivity to forcing factors and the incomplete representation of feedback processes 5 , 39 . Previous studies have suggested that feedbacks in response to insolation forcing, such as vegetation 18 , 40 43 , sea ice 44 47 , clouds 18 , and dust 48 , 49 , may have large impacts on temperatures, especially winter temperatures 18 , 41 43 , 46 . Although most of these feedbacks were incorporated into the TraCE-21ka simulation 5 , there are large uncertainties on feedbacks in the models 18 , 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Our control simulations, PI Control and MH Control, have orbital parameters, greenhouse gas concentrations, SSTs, and land surface parameters, including soil albedo and vegetation cover, set to PI and MH values, respectively (Table S1). Our prescription of MH vegetation included changes to plant functional type percentage and values of LAI ( Figure S1 and Table S2; Davies et al, 2015;Hoelzmann et al, 1998;Levis et al, 2004;Pausata et al, 2016). MH values for dry and saturated soil albedo are prescribed separately from vegetation (Table S2), and soil texture is not changed from PI values in any simulation.…”
Section: Model Experiments and Methodsmentioning
confidence: 99%
“…Some studies suggested that the shift of Green Sahara not only locally influenced the North African monsoon but also affected the large-scale atmospheric circulation and remotely influenced the Arctic climate (Davies et al 2015;Muschitiello et al 2015) and tropical climate (Pausata et al 2017a,b;Sun et al 2019) during the MH. Proxy data from the NW Iran suggested a wetter period during the early Holocene (9-6 ka BP), which was followed by a drier and dustier condition (Sharifi et al 2015).…”
Section: Using the Climate Simulations Based On The Projection Of Mh mentioning
confidence: 99%